Exploring Students’ Experiences in Developing Vocabulary through Reading Classic English Literature: A Qualitative Inquiry - Adelina, Yunita Sari (English Lecturers and Teachers Association (ELTA), 2025)
This research investigates the vocabulary development experiences of 30 fourth-semester students enrolled in the English Education Study Program at STKIP Al Maksum Langkat through their engagement with classic English literature. Although these students have received foundational English instruction, many still struggle to expand their vocabulary due to the limited contextual depth in their academic materials. To explore this issue, the study employed a qualitative design, gathering data through semi-structured interviews and reflective journals written after reading selected literary works by authors such as Shakespeare, Austen, and Dickens. The data were analyzed using open coding, category grouping, triangulation, and member checking procedures. Three major findings emerged. First, most participants (80%) relied on contextual cues, such as interpreting meanings from sentence structure and recording unfamiliar terms as key strategies for understanding new vocabulary. Second, a considerable number of students (73%) reported improvements in their vocabulary knowledge and linguistic sensitivity, including familiarity with idiomatic expressions and nuanced word meanings. Third, many learners (63%) encountered challenges, especially due to outdated vocabulary, lengthy sentence construction, and culturally unfamiliar content. These findings suggest that classic literature, when paired with reflective engagement and contextual support, can serve as a valuable medium for vocabulary enrichment in English language learning. The study recommends incorporating such texts into EFL curricula to foster deeper lexical acquisition and intercultural awareness.